Stimuli-Responsive Soft Untethered Grippers for Drug Delivery and Robotic Surgery - Ghosh, Arijit; Yoon, ChangKyu; Ongaro, Federico; Scheggi, Stefano; Selaru, Florin M.; Misra, Sarthak; Gracias, David H. (Frontiers in Mechanical Engineering, 2017)
Untethered microtools, that can be precisely navigated into deep in vivo locations, are important for clinical procedures pertinent to minimally invasive surgery and targeted drug delivery. In this mini-review, untethered soft grippers are discussed, with an emphasis on a class of autonomous stimuli responsive gripping soft tools that can be used to excise tissues and release drugs in a controlled manner. The grippers are composed of polymers and hydrogels, and are thus compliant to soft tissues. They can be navigated using magnetic fields and controlled by robotic path-planning strategies to carry out tasks like pick-and-place of microspheres and biological materials either with user assistance or in a fully autonomous manner. It is envisioned that the use of these untethered soft grippers will translate from laboratory experiments to clinical scenarios and the challenges that need to be overcome to make this transition are discussed.